2015
DOI: 10.1177/0309364614550261
|View full text |Cite
|
Sign up to set email alerts
|

Application of the skin and bone integrated pylon with titanium oxide nanotubes and seeded with dermal fibroblasts

Abstract: Study Design The feasibility and safety of in bone implantation of the skin and bone integrated pylons (SBIP) with nanotubes was investigated in vitro and in vivo in the animal model. Background Direct Direct skeletal attachment of limb prostheses is associated with high rate of transcutaneous infection and loosening of the fixture in the medullary canal prompting for careful assessment of various means for enhancing the skin-device and bone-device interface. The SBIP system constitutes a technological platf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 37 publications
(98 reference statements)
0
16
0
Order By: Relevance
“…Clearly, there will be a need to further extend this study to accommodate future developments in BAP including, but not limited to, growing number of consumers, broadening of case mix, changes to surgical procedures and constant developments of prosthetic components. 51,53,54 Effects of these changes in the economic evaluation of BAP over aids for non-prosthetic user (e.g. crutches, wheelchair) and other fitting options for prosthetic users (e.g.…”
Section: Generalisationmentioning
confidence: 99%
“…Clearly, there will be a need to further extend this study to accommodate future developments in BAP including, but not limited to, growing number of consumers, broadening of case mix, changes to surgical procedures and constant developments of prosthetic components. 51,53,54 Effects of these changes in the economic evaluation of BAP over aids for non-prosthetic user (e.g. crutches, wheelchair) and other fitting options for prosthetic users (e.g.…”
Section: Generalisationmentioning
confidence: 99%
“…The patented specifications of the implant include porosity, pore size, particle size and volume fraction of the material composition for sintering and the specific silver coating . High biointegrative and mechanical properties of the SBIP implants in various animal species including rats, mice, rabbits, and cats were demonstrated . The safety and sustainability of the skin‐device and bone‐device interface is provided for by the SBIP's composite porous structure, which promotes deep ingrowth of the hosting skin into the implanted pylon.…”
Section: Introductionmentioning
confidence: 99%
“…5 Previously, it was demonstrated that the nanostructured surface of the implants significantly improves the biocompatibility. 6 Nanostructured organization of the implants (eg, nanotubes, nanofibers, nanowires, and nanorods) promotes the integration of the implants with the surrounding bone tissues. [7][8][9][10][11][12] Thus, in the study by Seidling et al, the tested Ti implants with the nanostructured hyperhydrophilic chromosulfuric acid surface demonstrated 17-fold increase in the bone-to-implant contact and de novo bone formation in a gap healing model using Göttingen minipigs.…”
Section: Introductionmentioning
confidence: 99%